Unequal Exchange / A Study of Imperialism of Trade - Emmanuel Arghiri (Monthly Review Press, 1972)
Acknowledgments, Introduction, Equilibrium Prices in Internal Exchanges, Equilibrium Prices in External Exchanges, Wages, Limits and Implications of Unequal Exchange, The International Equilibrium Price with More than Two Factors, Comparative Costs, Conclusions, Appendices, Bibligraphy, Index.